Peran Brand Ambassador dan Tagline “Gratis Ongkir” Shopee Terhadap Keputusan Pembelian Shopee Pada Generasi Z di Kota Bandar Lampung - Azahra, Intan Nabila; Putri, Almira Devita (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
The research aims to determine whether or not brand ambassadors and taglines in Bandar Lampung City play a role in the buying habits of Generation Z. This research uses a quantitative approach. The respondents of this research are Gen Z in Bandar Lampung City who are Shopee users who have seen and are familiar with the Blackpink brand ambassador and Shopee's "Free Shipping" tagline in Bandar Lampung City. A total of 130 people were surveyed for this research sample. Non-probability sampling is used in this method. This research utilizes primary data collected by distributing questions online on Google. Multiple Linear Regression is used as a data analysis method. The linear regression results show the positive role of two variables on purchasing decisions. Apart from that, hypothesis testing shows that it was partially found that brand ambassadors and taglines play a positive and significant role in purchasing decisions. Meanwhile, simultaneously the brand ambassador and tagline play a significant role in purchasing decisions.